Implementasi Program Gerakan Literasi Sekolah di SMP Katolik St. Mikhael Brai -Watugong - Veronika Anjelina Dula; Abdullah Muis Kasim (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine and examine the implementation of the School Literacy Movement program at SMPK St. Mikhael Brai-Watugong. The research method used in this study is descriptive qualitative method. Data collection techniques used observation, interview and documentation techniques. The results showed that the implementation of the School Literacy Movement program at SMPK St Mikhael Brai-Watugong has been running in accordance with the guidelines for the School Literacy Movement set by the Ministry of Education and Culture (Kemendikbud) which consists of three stages, namely the habituation stage where students start reading habits for 15 minutes before the learning process begins, the development stage where students keep a daily literacy journal to prove that students have carried out literacy activities, and the learning stage where students read not only with books from the library but also from other media such as magazines, newspapers, and the internet. The supporting factors for the implementation of the School Literacy Movement program at SMPK St Mikhael Brai-Watugong are cooperation between school members, supervision of literacy activities, and facilities and infrastructure. Meanwhile, the inhibiting factors for the implementation of the School Literacy Movement program are the lack of students' interest in reading and the lack of reading books available at school.